The Primary School Teacher Readiness Through to Frequent Curriculum Changes in Indonesia: The Primary School Teacher Readiness Through to Frequent Curriculum Changes in Indonesia - Septian Airlanda, Gamaliel (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
Teacher performance uncertainty rumors occurs because of the frequent curriculum changes. This research aims to find the evidence of primary school teachers' readiness to face curriculum changes. The method of this research is quantitative descriptive with deductive analysis. The results show three evidence of primary school teachers' readiness for curriculum changes, such as: a) it is proven that almost every five years, the curriculum changed which is not ideal for teacher’s period in carrier; b) the ambiguity data of psychological readiness for primary school teachers towards curriculum changes was found between 53.5% and 46.5%; c) research proven that the effectiveness of the three learning domains exceeds 70% occurs because curriculum changes. This research also provides recommendations for a more meaningful curriculum change process. Through this research, it is hoped that rumors of teacher performance uncertainty can be scientifically proven and to be continued in finding solutions for improvement through recommendations that have been made.